The Exploration of EFL Teachers’ Technological Practices in Indonesian Schools - Mali, Yustinus Calvin Gai (Journal of English Teaching and Learning Issues, 2023)
Indonesian schools in the post-pandemic situation and after the release of the national policy in Indonesia encourage teachers to integrate technology into their teaching practices. This study involved 111 EFL teachers from 21 provinces in Indonesia to answer a set of questions in an online closed-ended questionnaire that specifically asked about the teachers’ frequency of using technology for EFL teaching and learning purposes, the kinds of technology they used, specific purposes of using the technology, and perceptions and challenges of using technology for the teaching and learning purposes. All the responses were exported and analyzed using Microsoft Excel to perform descriptive statistics to answer the research questions of this study. The data analysis showed that the teachers spend around 4 hours a week using various technology for their EFL teaching and learning practices. They also have positive perceptions towards the use of technology regardless of the limited time to use the technology and various external factors (i.e., limited school facilities, school policy about bringing phones to school, and students’ lack of technological skills) that might pose potential challenges when integrating technology in their classrooms. Notably, sharing English learning materials, giving tasks to their students, and finding material resources related to lessons are the most common reasons for teachers to use technology. Practical recommendations to enhance the teachers’ skills in using technology in Indonesian school settings and directions for future research are discussed.